Growth Response and Feed Utilization of Giant Gourami (Osphronemus goramy) Juvenile Feeding Different Protein Levels of the Diets Supplemented with Recombinant Growth Hormone - DARMAWAN SETIA BUDI; . ALIMUDDIN; MUHAMMAD AGUS SUPRAYUDI (Bogor Agricultural University, Indonesia, 2015)
The purpose of this study was to examine the effect of dietary supplementation with recombinant growth hormone (rGH) on the growth and dietary utility of juvenile giant gourami. The rGH was mixed with chicken egg yolk and sprayed on to artificial feed with different protein levels (34, 28, and 21%; isoenergy). Each treatment group of gourami was paired with a control group that received feed of the same protein level, but without rGH supplementation. Juvenile of giant gourami (weight 15.83 + 0.13 g) were fed diets containing rGH, to apparent satiation, 2 times a week. Fish were reared from less than 2 months old for 42 days in 100 L glass aquaria at an initial density of 10 fish per aquarium. At the end of this period, the biomass and daily growth rate (SGR) of the fish were measured and the feed conversion ratio calculated and compared. Our data showed that fish fed rGH-supplemented diets experienced higher growth than fish in the control groups and showed that fish with higher protein diets experienced higher growth than the groups with less protein diets. The group with the highest biomass gain, SGR, and lowest feed conversion ratio (FCR) was the group fed a 34% protein diet supplemented with rGH. Furthermore, biomass gain, SGR, and FCR in the rGH treatment group with a 28% protein diet matched the measurements of the non-rGH control group receiving a 34% protein diet (P > 0.05). We conclude that giant juvenile gourami given feed supplemented with recombinant growth hormone will experience increased growth and dietary utility compared with gourami given the same feed without supplementation.